In silico study for diversing the molecular pathway of pigment formation: an alternative to manual coloring in cotton fibers - Ahad, Ammara; Ahmad, Aftab; Din, Salahud; Rao, Abdul Qayyum; Shahid, Ahmad A.; Husnain, Tayyab (Frontiers in Plant Science, 2015)
Diversity of colors in flowers and fruits is largely due to anthocyanin pigments. The flavonoid/anthocyanin pathway has been most extensively studied. Dihydroflavonol 4-reductase (DFR) is a vibrant enzyme of the flavonoid pathway which displays major impact on the formation of anthocyanins, flavan 3-ols and flavonols. The substrate specificity of the DFR was found to play a crucial role in determination of type of anthocyanidins. Altering the flavonoid/ anthocyanin pathway through genetic engineering to develop color of our own choice is an exciting subject of future research. In the present study, comparison among four DFR genes (Gossypium hirsutum, Iris × hollandica, Ang. DFRI and DFRII), sequence alignment for homology as well as protein modeling and docking is demonstrated. Estimation of catalytic sites, prediction of substrate preference and protein docking were the key features of this article. For specific substrate uptake, a proline rich region and positions 12 plus 26 along with other positions emphasizing the 26-amino acid residue region (132-157) was tested. Results showed that proline rich region position 12, 26 and 132-157 plays an important role in selective attachment of DFRs with respective substrates. Further, ‘Expasy ProtParam tool’ results showed that Iris × hollandica DFR amino acids (Asn 9: Asp 23) favorable for reducing DHQ and DHM thus accumulating delphinidin, while Gossypium hirsutum DFR has (Asn 13: Asp 21) hypothesized to consume DHK. Protein docking data showed that amino acid residues in above mentioned positions were just involved in attachment of DFR with substrate and had no role in specific substrate uptake. Advanced bioinformatics analysis has revealed that all above mentioned positions have role in substrate attachment. For substrate specificity, other residues region is involved. It will help in color manipulations in different plant species.